2015
DOI: 10.12688/f1000research.6789.1
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated sodium channel as a target for metastatic risk reduction with re-purposed drugs

Abstract: Objective: To determine the exact role of sodium channel proteins in migration, invasion and metastasis and understand the possible anti-invasion and anti-metastatic activity of repurposed drugs with voltage gated sodium channel blocking properties. Material and methods: A review of the published medical literature was performed searching for pharmaceuticals used in daily practice, with inhibitory activity on voltage gated sodium channels. For every drug found, the literature was reviewed in order to define if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 122 publications
(103 reference statements)
0
32
0
Order By: Relevance
“…The use of ranolazine as a cardioprotective agent to reverse diastolic dysfunction may be viewed as a potential secondary prevention for late anthracycline cardiotoxicity. An interesting aspect of the potential use of ranolazine in oncological settings could also emerge from the current research showing that drugs targeting voltage-gated Na + channels may have anti-invasion and anti-metastatic effects (Djamgoz and Onkal, 2013;Driffort et al, 2014;Koltai, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The use of ranolazine as a cardioprotective agent to reverse diastolic dysfunction may be viewed as a potential secondary prevention for late anthracycline cardiotoxicity. An interesting aspect of the potential use of ranolazine in oncological settings could also emerge from the current research showing that drugs targeting voltage-gated Na + channels may have anti-invasion and anti-metastatic effects (Djamgoz and Onkal, 2013;Driffort et al, 2014;Koltai, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, early studies indicated that patients treated with these drugs had a significant reduction in HIV-associated tumors. 3 Further studies have demonstrated that Nelfinavir (NFR), one of the first HIV-PIs to be approved by the FDA, showed promising anticancer properties in mice and in non-infected cancer patients. This led to phase I and phase II clinical trials that were designed to evaluate NFR repositioning in various cancer types.…”
mentioning
confidence: 99%
“…This led to phase I and phase II clinical trials that were designed to evaluate NFR repositioning in various cancer types. 3 Nevertheless, the mechanisms underlying NFR and HIV-PIs anti-tumoral properties remained poorly understood. 3 In a previous study we showed that NFR targets translation program by inducing the integrated stress response (ISR).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ranolazine was found previously also to reduce metastatic dissemination in a breast cancer xenograft model [167]. Thus, ranolazine and other available VGSC/INaP blockers could be 'repurposed' as novel anti-metastatic drugs in clinical management of CRC [168][169][170][171].…”
Section: P53 Pathway In Colorectal Cancermentioning
confidence: 96%